2012
DOI: 10.4304/jcp.7.6.1429-1436
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of Harmonic Gear Drives Considering Tooth Profiles Parameters Optimization

Abstract: Abstract-Considering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Therefore, based on the above discussions, the design variables are defined as the following: pinion teeth number z 1 of high-speed stage, module m 1 , helix angle β 1 , transmission ratio u 1 ; pinion teeth number z 3 , module m 2 , and helix angle β 2 . The seven design variables are shown in (1).…”
Section: A Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the above discussions, the design variables are defined as the following: pinion teeth number z 1 of high-speed stage, module m 1 , helix angle β 1 , transmission ratio u 1 ; pinion teeth number z 3 , module m 2 , and helix angle β 2 . The seven design variables are shown in (1).…”
Section: A Mathematical Modelmentioning
confidence: 99%
“…And in this paper, the objective function is selected as the total minimum center distance, which seeks the minimum sum of center distances. The objective function can be expressed as shown in (2) using the design variables in (1).…”
Section: A Mathematical Modelmentioning
confidence: 99%
“…In a sliding-vane rotary pump (or a balanced vane-type pump) having a number of vanes which are free to slide into or out of slots in the pump rotor, two discharge cavities placed diametrically opposite each other keep the rotor in hydraulic balance, relieving the bearings of heavy loads [6,7]. Inspired by this, we conceived a new gear pump with flexible ring gear by combining the characteristics of harmonic gear drive [10,11] with the working principle of gear pump. Figure 1 presents a sketch of the new gear pump, the main components include pump body (1), end cover, pinion (2), flexible ring gear (4), sealing block (5), roller (3) and side plate (6).…”
Section: Features Of Gear Pump With Flexible Ring Gearmentioning
confidence: 99%
“…Dong et al [21] optimized the circular spline (CS) tooth profile to decrease dynamic loads during meshing and avoid FS fatigue fracture. The analysis revealed that about 18% of the teeth participate to the sharing of the contact force.…”
Section: Introductionmentioning
confidence: 99%